An Insight Into COVID-19: A 21st Century Disaster and Its Relation to Immunocompetence and Food Antioxidants - Siddique, Faisal; Abbas, Rao Zahid; Mansoor, Muhammad Khalid; Alghamdi, Etab Saleh; Saeed, Muhammad; Ayaz, Muhammad Mazhar; Rahman, Moazur; Mahmood, Muhammad Shahid; Iqbal, Asif; Manzoor, Maida; Abbas, Asghar; Javaid, Asif; et al. (Frontiers in Veterinary Science, 2021)
Coronavirus Disease 2019 (COVID-19) ranks third as a fatal coronavirus disease threatening public health after SARS-CoV (severe acute respiratory syndrome coronavirus) and MERS-CoV (Middle East respiratory syndrome coronavirus). SARS-CoV-2 (severe acute respiratory syndrome, coronavirus type 2) causes COVID-19. On 30 January 2020, the World Health Organization (WHO) announced that the COVID-19 outbreak is the sixth global health emergency. As of 03 December 2020, sixty-four million people worldwide have been affected by this malaise, and the global economy has experienced a loss of more than $1 trillion. SARS-CoV-2 is a positive-sense single-stranded RNA virus belonging to the Betacoronavirus genus. The high nucleotide sequence identity of SARS-CoV-2 with BatCoV RaTG13 genome has indicated that bats could be the possible host of SARS-CoV-2. SARS-CoV-2 penetrates the host cell via binding its spike protein to the angiotensin-converting enzyme 2 (ACE2) receptor, similar to the mechanisms of SARS-CoV and MERS-CoV. COVID-19 can spread from person to person via respiratory droplets and airborne and contaminated fomites. Moreover, it poses a significant risk to smokers, the elderly, immunocompromised people, and those with preexisting comorbidities. Two main approaches are used to control viral infections, namely, vaccination and biosecurity. Studies to analyze the antigenicity and immunogenicity of SARS-CoV-2 vaccine candidates are underway, and few vaccines may be available in the near future. In the current situation, the Human Biosecurity Emergency (HBE) may be the only way to cope effectively with the novel SARS-CoV-2 strain. Here, we summarize current knowledge on COVID-19 origin, epidemiological relationship with humans and animals, genomic resemblance, immunopathogenesis, clinical-laboratory signs, diagnosis, control and prevention, and treatment. Moreover, we discuss the interventional effects of various nutrients on COVID-19 in detail. However, multiple possibilities are explored to fight COVID-19 with the greatest efforts targeted towards finding an effective vaccine in the near future. Furthermore, antioxidants, polyphenols, and flavonoids both synthetic and natural could play a crucial role in the fight against COVID-19.